The Effects of Injection Strategy on the Performance and Emission Characteristics of a Premixed Charge Compression Ignition Engine - Ha, Khuong Thi; Cao, Nguyen Van; Tuan, Le Anh (Engineering, Technology & Applied Science Research, 2026)
This study presents an experimental analysis of the combustion characteristics, performance, and emission behavior of a diesel engine operating with the Premixed Charge Compression Ignition (PCCI) combustion, which was achieved by altering injection parameters, such as timing, pressure, and duration, at an engine speed of 1,800 RPM and a load of 20%. The results show that early injection timing improves mixture preparation while creating a low-temperature heat release (cool flame) and a pressure of 450 bar, which were optimal for stable PCCI operation. Under these conditions, efficiency increased by 10–12% compared to conventional diesel combustion, while the rate of pressure rise remained below the knock threshold. PCCI combustion resulted in substantial reductions in Nitrogen Oxides (NOx) and smoke emissions, due to lower peak combustion temperatures and more homogeneous mixture formation. However, unburned Hydrocarbon (HC) and Carbon Monoxide (CO) emissions increased due to reduced oxidation rates and incomplete combustion under low temperatures.